Resveratrol Promotes Diabetic Wound Healing via SIRT1-FOXO1-c-Myc Signaling Pathway-Mediated Angiogenesis - Huang, Xiaozhong; Sun, Jia; Chen, Gen; Niu, Chao; Wang, Ying; Zhao, Congcong; Sun, Jian; Huang, Huiya; Huang, Shuai; Liang, Yangzhi; Shen, Yingjie; Cong, Weitao; et al. (Frontiers in Pharmacology, 2019)
Background/Aims: Diabetic non-healing skin ulcers represent a serious challenge in clinical practice, in which the hyperglycemia-induced disturbance of angiogenesis, and endothelial dysfunction play a crucial role. Resveratrol (RES), a silent information regulator 1 (SIRT1) agonist, can improve endothelial function and has strong pro-angiogenic properties, and has thus become a research focus for the treatment of diabetic non-healing skin ulcers; however, the underlying mechanism by which RES regulates these processes remains unclear. Therefore, the present study was intended to determine if RES exerts its observed protective role in diabetic wound healing by alleviating hyperglycemia-induced endothelial dysfunction and the disturbance of angiogenesis. Methods: We investigated the effects of RES on cell migration, cell proliferation, apoptosis, tube formation, and the underlying molecular mechanisms in 33 mM high glucose-stimulated human umbilical vein endothelial cells (HUVECs) by semi-quantitative RT-PCR, western blot analysis, terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining, and immunofluorescence in vitro. We further explored the role of RES on endothelial dysfunction and wound healing disturbance in db/db mice by TUNEL staining, immunofluorescence, and photography in vivo. Results: We observed an obvious inhibition of hyperglycemia-triggered endothelial dysfunction and a disturbance of angiogenesis, followed by the promotion of diabetic wound healing via RES, along with restoration of the activity of the hyperglycemia-impaired SIRT1 signaling pathway. Pretreatment with EX-527, a SIRT1 inhibitor, abolished the RES-mediated endothelial protection and pro-angiogenesis action, and then delayed diabetic wound healing. Furthermore, examination of the overexpression of forkhead box O1 (FOXO1), a transcription factor substrate of SIRT1, in HUVECs and db/db mice revealed that RES activated SIRT1 to restore hyperglycemia-triggered endothelial dysfunction and disturbance of angiogenesis, followed by the promotion of diabetic wound healing in a c-Myc-dependent manner. Pretreatment with 10058-F4, a c-Myc inhibitor, repressed RES-mediated endothelial protection, angiogenesis, and diabetic wound healing. Conclusion: Our findings indicate that the positive role of RES in diabetic wound healing via its SIRT1-dependent endothelial protection and pro-angiogenic effects involves the inhibition of FOXO1 and the de-repression of c-Myc expression.